2007
DOI: 10.1111/j.1444-2906.2007.01303.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary medicinal herbs improve growth performance, fatty acid utilization, and stress recovery of Japanese flounder

Abstract: Some effects of dietary medicinal herbs mixture (HM), Massa medicata fermentata, Crataegi fructus, Artemisia capillaries, and Cnidium officinale, in the proportions 2:2:1:1 were identified in juvenile Japanese flounder Paralichthys olivaceus. In an 8-week feeding trial, fish were fed with 0.1, 0.3, 0.5, and 1.0% HM in a moist diet composed of horse mackerel and an artificial diet in equal parts. Fish fed the diets with 0.3, 0.5, and 1.0% HM showed higher weight gain and feed efficiency than fish in 0.1 and 0% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
70
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 14 publications
11
70
2
Order By: Relevance
“…Increase in haemoglobin content (Hb), haematocrit, and numbers of leukocytes and thrombocyte were reported in Nile tilapia (Shalaby et al 2006), hybrid tilapia (Ndong and Fall 2011) fed diet enriched by garlic. These results are in agreement with previous research in which feeding with other herbal supplemented feed led to an increase in erythrocyte-and leukocyte count, haemoglobin level and haematocrit (Martins et al 2002, Ji et al 2007). …”
Section: Discussionsupporting
confidence: 83%
“…Increase in haemoglobin content (Hb), haematocrit, and numbers of leukocytes and thrombocyte were reported in Nile tilapia (Shalaby et al 2006), hybrid tilapia (Ndong and Fall 2011) fed diet enriched by garlic. These results are in agreement with previous research in which feeding with other herbal supplemented feed led to an increase in erythrocyte-and leukocyte count, haemoglobin level and haematocrit (Martins et al 2002, Ji et al 2007). …”
Section: Discussionsupporting
confidence: 83%
“…They found reduced glucose concentrations in the aquatic animals fed with herbal immunostimulant diets. Furthermore, Ji et al (2007) reported low blood glucose concentrations and plasma glutamic oxaloacetic transaminase in juvenile Japanese flounder fed with herbal mixtures. The decrease of glucose concentrations might be due to the capability of plant oils to reduce the effects of stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that when these bacteria are administered to the shrimp as probiotics, growth, survival, digestive enzyme activity, and apparent digestibility coefficients of nutrients were improved and immunity was enhanced (Rengpipat et al 1998;Rengpipat et al 2000;Saeed et al 2006;Lin et al 2004). Medicinal herbs (MH) have been used as popular medicines to secure health and longevity in land mammals and humans in Asia, especially China, India, Japan, and Korea (Ji et al 2007b). There is a developing interest in using MH as a kind of dietary supplement in aquaculture, and in showing the positive effects on growth and the immune response (Ji et al 2007b;Jung et al 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Medicinal herbs (MH) have been used as popular medicines to secure health and longevity in land mammals and humans in Asia, especially China, India, Japan, and Korea (Ji et al 2007b). There is a developing interest in using MH as a kind of dietary supplement in aquaculture, and in showing the positive effects on growth and the immune response (Ji et al 2007b;Jung et al 2002). MH can improve the quantity of microflora in the intestine by increasing some good microbes and inhibiting some microbial pathogens (Liu et al 2004).…”
Section: Introductionmentioning
confidence: 99%